Thrombogenic responses from electrocured tissue adhesives - Nanda, Himansu Sekhar (2019)
Electrocured tissue adhesives offer a new route towards addressing unmet surgical challenges in tissue fixation. We have recently developed an electrocuring adhesive (aka Voltaglue) by grafting carbene precursors on polyamidoamine (PAMAM) G5 dendrimers. The cationic adhesive can be cured through low-voltage activation and exhibits voltage and time dependent crosslinking, allowing some control over material and adhesive properties. Herein, we have evaluated the platelet adhesion and activation of the bioadhesives electrocured with applied voltages of 5V and 10V. The electrocured bioadhesives exhibited platelet resistant properties that was dependent on voltage magnitude.